Polysaccharides from by-products of the Wonderful and Laffan pomegranate varieties: New insight into extraction and characterization. (15th November 2017) - Khatib, Mohamad; Giuliani, Camilla; Rossi, Federico; Adessi, Alessandra; Al-Tamimi, Amal; Mazzola, Giuseppe; Di Gioia, Diana; Innocenti, Marzia; Mulinacci, Nadia
Highlights: The highest extractive yields of polysaccharides were obtained by 1 h of decoction. Polysaccharides profiles by SEC were similar for the Laffan and Wonderful varieties. 1 H NMR confirmed the presence of pectin at different methylation/acylation degree. Crude polysaccharides from Laffan and Wonderful showed in vitro prebiotic properties. Abstract: The main crude polysaccharides (CPS), extracted from two widely cultivated pomegranate varieties, Laffan and Wonderful, were studied and characterized. We obtained the highest CPS extraction yield (approximatively 10% w/w on dried matter) by 1 h of decoction (ratio 1/40 w/v). The predominant polymers (75–80%) of the CPS samples showed a hydrodynamic volume close to 2000 kDa by size exclusion chromatography and the exocarp and mesocarp profiles were very similar. The proton spectra ( 1 H NMR), according to sugar composition and gelling ability, confirmed the main polysaccharide fractions were pectin with different acylation and methylation degree. The CPS from Laffan and Wonderful mesocarp showed prebiotic properties in vitro with Lactobacillus and Bifidobacterium strains. The composition of the decoction (12% ellagitannins and 10% of CPS) obtained by a green extraction process of pomegranate by-products, makes it a suitable component of functional food formulations.